(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the content and current state of the development of professional competence of teachers based on digital technologies and thus the education of a potential teacher. It also describes the principles of education aimed at training professional teachers, and mentions ways to increase the competence of teachers in the use of digital technologies and the use of its capabilities in the development of professional competence of teachers.